Detinization of the economy in the context of overcoming crisis phenomena caused by the COVID-19 pandemic - I.V. Suprunova (Економіка, управління та адміністрування, 2020)
A critical analysis of the dynamics of forecasted values of gross domestic product (GDP) in Ukraine and in the world under uncertainty. It should be noted that the depth of the economic downturn will depend on many factors, such as: the development of a pandemic, the duration and intensity of restrictive measures, negative changes in economic processes, fluctuations in the financial market, changes in human behavior. The adjusted forecasts of economic development of the International Monetary Fund, the World Bank, the Organization for Economic Cooperation and Development for changes in the gross domestic product of the world's leading countries as a result of the spread of SARS-CoV-2 virus at an exponential rate. A comparison of economic development forecasts for 2020–2021 for Ukraine is provided on the basis of published reports of the International Monetary Fund, the World Bank, the Cabinet of Ministers of Ukraine, the Ministry of Economic Development, Trade and Agriculture of Ukraine and the National Bank of Ukraine. It is established that in the conditions of aggravation of crisis situation the share of shadow processes in economy grows and there is a necessity of change of tools and methods of the state management of shadow economy as a structural component of state security, improvement of the mechanism of de-shadowing policy. The internal and external risks associated with the COVID-19 pandemic are highlighted. In the context of the study, the shadow economy is considered in the system of state security and is interpreted as a socio-economic phenomenon, which is characterized by uncontrolled and unregulated, informal and illegal economic relations that threaten national security and cause economic, social and environmental damage to the state and society. Measures to overcome the crisis caused by the COVID-19 pandemic and de-shadow the economy are suggested.